The Causal Impacts of Child Labor Law in Brazil : Some Preliminary Findings - Piza, Caio; Portela Souza, André (World Bank, Washington, DC, 2015)
This paper investigates the causal impact of the change in Brazil’s child labor law of December 1998. The change increased the minimum legal age of entry into the labor force from 14 to 16 years. The analysis uses a difference-in-differences approach to estimate the impact of this change in the law on labor force participation rates as a whole, as well as for the formal and informal sectors separately. The results show that the ban reduced participation rates for boys by 4 percentage points and that this effect was mostly driven by the informal sector. No effect is found for girls.